Average bioequivalence of single 500 mg doses of two oral formulations of levofloxacin: a randomized, open-label, two-period crossover study in healthy adult Brazilian volunteers - Eunice Kazue Kano; Eunice Emiko Mori Koono; Simone Grigoleto Schramm; Cristina Helena dos Reis Serra; Eduardo Abib Junior; Renata Pereira; Márcia Sayuri Takamatsu Freitas; Maria Cristina Iecco; Valentina Porta (Universidade de São Paulo, 2015)
Average bioequivalence of two 500 mg levofloxacin formulations available in Brazil, Tavanic(c) (Sanofi-Aventis Farmacêutica Ltda, Brazil, reference product) and Levaquin(c) (Janssen-Cilag Farmacêutica Ltda, Brazil, test product) was evaluated by means of a randomized, open-label, 2-way crossover study performed in 26 healthy Brazilian volunteers under fasting conditions. A single dose of 500 mg levofloxacin tablets was orally administered, and blood samples were collected over a period of 48 hours. Levofloxacin plasmatic concentrations were determined using a validated HPLC method. Pharmacokinetic parameters Cmax, Tmax, Kel, T1/2el, AUC0-t and AUC0-inf were calculated using noncompartmental analysis. Bioequivalence was determined by calculating 90% confidence intervals (90% CI) for the ratio of Cmax, AUC0-t and AUC0-inf values for test and reference products, using logarithmic transformed data. Tolerability was assessed by monitoring vital signs and laboratory analysis results, by subject interviews and by spontaneous report of adverse events. 90% CIs for Cmax, AUC0-t and AUC0-inf were 92.1% - 108.2%, 90.7% - 98.0%, and 94.8% - 100.0%, respectively. Observed adverse events were nausea and headache. It was concluded that Tavanic(c) and Levaquin(c) are bioequivalent, since 90% CIs are within the 80% - 125% interval proposed by regulatory agencies.